Oral Exposure to TiO2 and Cellulose Nanomaterials: review of hazard identification in the adverse outcome pathway landscape - Rolo, Dora (2022)
Several products in the global market have been improved using titanium dioxide nanomaterials (TiO2 NMs), and many other NMs under development, e.g., cellulose NMs(CNMs), with potential for use in agriculture, food, and feed industries. Despite being considered key enabling technologies, the exponential use of NMs in food technology leads to concerns about adverse health outcomes upon ingestion, such as potential genotoxicity and cancer of the gastrointestinal tract (GIT) due to their bioaccumulation. The aim of this study, considering oral exposure to TiO2 NMs and CNMs as case studies, was to explore the knowledge about these NMs’ cellular and molecular mechanisms of action that may be central to their predicted adverse outcomes pathways at the GIT. For this purpose, literature reviews were setup to target the hazard of these NMs in the GIT context, directed to identify the molecular initiating event (MIE) and key events (KE) that mediate potential genotoxic and carcinogenic effects, thus contributing to Adverse Outcome Pathways (AOP) landscape. From the review of in vitro/in vivo studies, the suggested MIE involves the cellular uptake by intestinal cells and effects at lysosomal level. Several possible KE like inflammation, persistent cell injury/cell death, ROS generation, and DNA damage that may mediate the formation of adenomas/carcinomas were identified for TiO2 NMs; the information for CNMs is scarce. Some knowledge gaps were also identified, opening new avenues for more mechanistic research that will feed into AOPs.